Curriculum reorganization and courses' collaboration in computer science - Ristov, Sasko; Jovanov, Mile; Gushev, Marjan; Mihova, Marija (IEEE, 2016)
Teaching a hardware-based course for computer science students is a very challenging task. Students need to do a lot of practical work in the laboratory, usually do some practical project, learn theory and finally take the exam. This is a very hard task for the first hardware-based course - Computer architecture and organization (CAO), especially if it is offered in the first year of studies. Many successful examples report introducing some online learning tools, such as distance laboratories or visual simulators, which help students easier to learn the required learning objectives. In this paper, we introduce a brand new approach of reorganizing the curriculum of the course of Discrete Mathematics (DM). This approach transfers the fundamentals of logic design earlier in the DM course. Since both DM and CAO courses are scheduled in parallel, this transfer and reorganization offers necessary background for topics learned in the CAO course. This change prepares the students with relevant content about digital logic part of the CAO course and results with an improvement of 50% of those who had passed the midterm exam compared to the previous years.
Keywords: Computer science; digital logic; computer architecture and organization; discrete mathematics; curriculum